MANIFESTASI PROGRAM KESEJAHTERAAN SOSIAL ANAK (PKSA) DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL ANAK JALANAN DI RUMAH SINGGAH ANAK MANDIRI (RSAM) YOGYAKARTA - Aulia Widya Sakina; Yuli Setyowati; Oktarina Albizzia; Anastasia Adiwirahayu (Universitas Jenderal Ahmad Yani, 2020)
The phenomenon of street children is one of the crucial problems that accompany the development process. The dynamics of the life of street children which are identical with the culture of poverty, are considered to deviate from the social function of children due to various activities carried out on the streets. Over the past 9 years, the Ministry of Social Affairs has implemented policies, strategies and Program Kesejahteraan Sosial Anak (PKSA) which aims to empower and meet the needs of children living on the streets, however these efforts are seen as not yet running optimally. Echoes of